2007
DOI: 10.1128/jvi.00758-07
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Residues That Form Putative Fusion Loops of Epstein-Barr Virus Glycoprotein B Are Critical for Fusion Activity

Abstract: To test the importance of the hydrophobic residues within the putative Epstein-Barr virus (EBV) glycoprotein B (gB) fusion loops in membrane fusion, WY 112-113 and WLIW [193][194][195][196] were mutated into alanine, glutamic acid, or the analogous residues from herpes simplex virus type 1 (HSV-1) gB (HR and RVEA). All gB variants exhibited cell surface expression, demonstrating that the substitutions did not perturb gB trafficking. None of six gB variants was, however, capable of mediating fusion with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 37 publications
2
51
1
Order By: Relevance
“…Indeed, these loops are much less hydrophobic than the amino-terminal fusion peptides of class I proteins (even when the three fusion domains of G are grouped together in the post-fusion conformation). That these loops are indeed an essential part of the membrane interacting motif is consistent with previous mutagenesis work performed on rhabdoviruses [59,60] (Table 1) and has since been confirmed for both VSV G [61] (Table 1) and Herpesviruses gB [62,63].…”
Section: Interaction Between Fusion Domains and Membranessupporting
confidence: 88%
“…Indeed, these loops are much less hydrophobic than the amino-terminal fusion peptides of class I proteins (even when the three fusion domains of G are grouped together in the post-fusion conformation). That these loops are indeed an essential part of the membrane interacting motif is consistent with previous mutagenesis work performed on rhabdoviruses [59,60] (Table 1) and has since been confirmed for both VSV G [61] (Table 1) and Herpesviruses gB [62,63].…”
Section: Interaction Between Fusion Domains and Membranessupporting
confidence: 88%
“…In contrast, the fusion loops of class II fusion proteins and herpesvirus gB are buried at an oligomeric interface. Interestingly, mutation of the hydrophobic residues of the gB fusion loop did not cause any generalized problem in protein trafficking to the cell surface (48,49). In contrast, we found that even conservative changes in the hydrophobic residues of the VSV G fusion loops caused significant problems in protein transport to the cell surface.…”
Section: Discussioncontrasting
confidence: 37%
“…Both VSV (Rhadboviridae) and HSV-1 (Herpesviridae) belong to an extended family of viruses with equivalent fusion domains. In the case of the herpesviruses, the Epstein-Barr virus and human herpesvirus 6, 7, and 8 gB homologs all appear to have more exposed tryptophan residues (49), with in one case (Epstein-Barr virus) three tryptophan residues present (50). Animal rhabdoviruses in general have a single tryptophan residue in their fusion loops.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 h, the medium was changed, and at 24 h posttransfection, cells were detached with Versene and transferred to Corning 96-well plates, using 3 wells per sample. After incubation for 24 h at 37°C, cells were washed with PBS-ABC (PBS with 0.89 g of CaCl 2 and 0. Immunoprecipitation.…”
Section: Cells and Antibodiesmentioning
confidence: 99%